Tinjauan Yuridis Akibat Hukum Terhadap Wanprestasi dalam Perjanjian Kredit - Marpaung, Peter Baringin; Arifin, Syamsul; Hidayani, Sri (Universitas Medan Area, 2016)
of the action that is contrary to the law, especially with the provisions of civil law is an act of violation in the agreement or denying an agreement that has been agreed upon by both parties. Agreement or bad violations in an agreement or often referred to as legality in the language. The problems that will be discussed are in accordance with the judges' judgments in law enforcement and the making of decisions on defaults. The purpose of this study is to get answers to the problems faced. The research method with decision research (library research) is a method by conducting research on various sources of written reading. Field Research (Field Research), namely by conducting field research Medan District Court. The legal consequences of defaults on credit agreements do not rule out the possibility of one party being sanctioned, that is, the plaintiff or defendant because not all plaintiffs' claims will be received in court, and vice versa, do not reject the defendant's conception. Regarding the sanctions, the defendant can be charged a fee or pay a loss and pay fees charged to the plaintiff.